(untitled) (Journal of Fatima Jinnah Medical University, 2019)
Background: Ethiodized oild (Lipoidol®) is a commonly used but an expensive oil-based carrier to facilitate injection Histoacryl® (N-butyl-2-Cyanoacrylate) to treat gastric varices. This study evaluates the efficiency and safety of olive oil as a cheaper oil-based carrier for injecting Histoacryl® (N-butyl-2-Cyanoacrylate) to obliterate gastric varices endoscopically. Subject and Methods: This prospective observational study was carried out at Gastroenterology Department, Lahore General Hospital, Lahore from January 2014 to December 2016. Total of 132 patients of gastric varices diagnosed on upper gastrointestinal endoscopy and obliterated using Histoacryl® injections mixed with olive oil were enrolled. Sarin’s classification was used to classify the gastro-oesophageal varices (GOV) into four types. Successful hemostasis was defined as hemodynamic stabitility, no rebleeding episode and no further drop in hemoglobin within 24 hours following sclerotherapy. Results: According to Sarin classification, 69 (52.3%), 56 (42.4%) and 7 (5.3%) patients had GOV2, GOV1 and isolated gastric varices respectively. Mean age was 57.3 year and 87 (65.9%) patients were male. Large bulging varices with visible platelet plug were present in 84% patients. Out of 132 patients, 92 (69.69%), 34 (25.75%) and 6 (0.04%) patients received 1, 2 and 3 sessions respectively. Successful hemostasis after first injection was achieved in 128 (97%) cases. Twenty five (18.9%) patients presented with re-bleeding in six months and the rate of re-bleed was higher in GOV2. No immediate or long-lasting complications for Histoacryl® (N-butyl-2-cyanoacrylate) injection mixed with olive oil occurred in these cases during follow-up. Conclusion: Histoacryl® injection with olive oil based carrier is an equally effective, rapid, easy, cheap and alternative for routine clinical use in endoscopic treatment of gastric varices.